The effectiveness of passive design strategies for a mosque in Malaysia : case studies of Putra Mosque and Tuanku Mizan Zainal Abidin Mosque - Tengku Anis Qarihah binti Raja Abdul Kadir (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2015)
Malaysia has a tropical climate with warm and humid weather all year round. It is usually very hot and humid, especially in the major cities. Malaysia is the best country to study on the passive design strategies in tropical climates. Since the time of our ancestors, buildings had been built characterized by passive design where it focused on a balance between local climate, surrounding areas, functions, appearances and design of the buildings. Passive design strategies can defined as the measures that had been taken to ensure the comfort of the occupant achieved. It must have a closer relationship with its surroundings to achieve a comfortable internal environment with a minimum of resource used. However, in this modern age, most of the building neglected the beauty of passive design strategies and end up relying on active design strategies such as air conditioning systems and others. This research will discuss the importance of passive design strategies and knowing its effectiveness against the user's comfort, energy efficiency and the visual impact on the user's point of view. Characteristic of passive design strategies taken from the Malaysian Standard: MS1525. MS1525 is the Code of Practice on Energy Efficiency and use of Renewable Energy for Non-Residential Buildings, which was developed to provide the best practice in energy efficiency for buildings. Two case studies involved are Putra Mosque and Sultan Mizan Zainal Abidin Mosque. Both federal mosques have a different approach to passive design techniques that comparative studies between both cases studies, help to evaluate the effectiveness of passive design strategies and the perception of user's preferences. Other than that, questionnaires, interviews, field works and data collections conducted as primary data to justify the results. This research will help designers to determine the characteristic of the passive design strategies that effective in giving comfort to people, reducing energy consumption and add beauty to a building as a whole.